IMPLEMENTASI WEB SERVICE PADA PORTAL UNIVERSITAS TANJUNGPURA SEBAGAI MEDIA PENDUKUNG MANAJEMEN CONTENT - Arifanto, Randy (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2015)
Web service is a software system designed to support machine to machine interaction over a network. Advantages offered in the web service is the ability to perform communication between different systems of database and servers. In a university course, there are a variety of web-based services. By using web services, data synchronization between the service will be easy to do. Therefore web service implemented as a supporting media content management Tanjungpura University portal. Web service is implemented in terms of news management and implementation of SSO (Single Sign On). In the news management, with the implementation of web service, the news contained in the Tanjungpura University portal not only from the portal database itself but also can be derived from the database of faculty websites and websites that are in the Tanjungpura University environment. While the SSO implementation, with the implementation of web service users can use the Tanjungpura University services simply by doing one-time login process. From the analysis of the test results it can be concluded that the web service has been successfully applied as supporting media news management, web services has been successfully applied as a supporting media single sign-on system, and the whole system has been implemented properly.